(untitled) (Journal of Reviews on Global Economics, 2019)
Previous studies have evident the effects of oil price changes on domestic inflation. However, such effects may vary due to oil dependency factor. This paper extends the examination on two panel groups, namely the oil importing and oil exporting countries. Each group consists of ten countries. Besides, we also compare the relative effects of oil price with other shocks (domestic output, exporter’s production cost and real exchange rate) on domestic inflation (consumer price and producer price). Our results capture significant pass-through effect from oil price changes on domestic inflation at producer and consumer levels. However, oil price is not the main determinant to domestic inflation. The oil price pass-through effect differs between oil importing versus oil exporting groups across consumer and producer levels. Higher oil price causes to higher production price inflation but does not lead to higher consumer price inflation in both groups of countries. The oil price effect together with exchange rate, foreign cost production and GDP have significant long-run impact on domestic inflation in both groups of countries. The joint effects are small and not significant in the short-run. Oil dependency and effective monetary policy matter on determining the effect of oil price changes on domestic inflation.